Clinical implications of a gain-of-function genetic polymorphism in DPYD (rs4294451) in colorectal cancer patients treated with fluoropyrimidines - De Mattia, Elena; Polesel, Jerry; Scarabel, Lucia; Cecchin, Erika (Frontiers in Pharmacology, 2024)
Dihydropyrimidine dehydrogenase (DPD, encoded by the DPYD gene) is the rate-limiting enzyme for the detoxification of fluoropyrimidines (FLs). Rs4294451 is a regulatory DPYD polymorphism that has recently been functionally characterized and associated with increased DPD expression in the liver. The aim of the present study was to test the clinical implications of being a carrier of rs4294451 in a cohort of 645 FL-treated colorectal cancer patients. Carriers of at least one DPYD rs4294451-T variant allele had a lower risk of developing NCI-CTC grade 4–5 hematological [odds ratio (OR) = 0.39; 95% confidence interval (CI): 0.15–0.98; additive model] and hematological/non-hematological (OR = 0.44; 95% CI: 0.22–0.88; dominant model) FL-related toxicity. Patients with the DPYD rs4294451-T allele also had a longer time to severe toxicity development after starting FL treatment [hematological, Hazard ratio (HR) = 0.27; 95% CI: 0.09–0.79; Fine–Gray test = 0.1569; hematological/non-hematological: HR = 0.38, 95% CI: 0.17–0.85; Fine–Gray test = 0.0444]. It is worth noting that while being at lower risk of toxicity, DPYD rs4294451-T allele carriers also tend to present a shorter overall survival (HR = 1.41; 95% CI: 1.05–1.90; log-rank p = 0.0406). These findings demonstrate a clinical effect of DPYD-rs4294451 polymorphism coherent with the recently described functional effect. Further investigation is warranted to elucidate the potential clinical value to the rs4294451 polymorphism as toxicity and especially as an efficacy marker in colorectal cancer.